Physicochemical Properties of Traditionally Produced Mead - Kristina Habschied; Blanka Bilić Rajs; Lorena Dozan; Vinko Krstanović; Krešimir Mastanjević (Beverages, 2025)
Mead is described as a traditional alcoholic drink produced by fermentation from a solution of honey and water. It has been produced as a refreshing drink. However, in the past, it was more expensive than wine, which led to a decrease in demand. Due to the simple method of production, the mead industry is growing again. The quality and physicochemical properties of mead depend on the type of honey used. The goal of this study is to produce mead from two kinds of honey of different floral origins, chestnut and sunflower, in order to determine the differences using sensory and physicochemical analyses. The fermentation process was monitored until the extract values were consecutively the same. The results obtained in this research indicate that chestnut honey mead took a longer time to ferment, 2 months, while sunflower honey mead took 1.5 months to ferment. The alcohol content in chestnut honey mead was 7.2% v/v, and sunflower honey mead contained 8.6% v/v. Sensory-wise, the chestnut mead was more acceptable to consumers due to a more pronounced color and thus received a one-point higher score (15) than sunflower honey mead (14).